Analysis of Various Complex Flows of Micropolar Fluids in the Slip Flow Regime - Kamram, Muhammad (Curtin University, 2018)
Four mathematical models have been developed to study the slip flow of micropolar fluids over a stretching/shrinking sheet under the influence of slip and the Newtonian heating conditions at the boundary. The optimal homotopy analysis method is applied for the solutions of these models. The results obtained from this study are useful in liquid crystals, polymeric suspensions, polishing artificial heart valves and internal cavities.